The environmental history of Fenékpuszta with a special attention to the climate and precipitation of the last 2000 years - Sümegi, Pál; Törőcsik, Tünde; Jakab, Gusztáv; Gulyás, Sándor; Pomázi, Péter; Majkut, Péter; Páll, Dávid Gergely; Persaits, Gergő; Bodor, Emese (Journal of Environmental Geography, 2009)
This work presents the details of a multidisciplinary palaeoecological and geoarcheological study on the sedimentary sequences, including 2 undisturbed cores of the Little Balaton situated in the western part of Lake Balaton in Central Europe. The application of Quaternary palaeoecological analysis to peat and lacustrine deposits enables to identify long-term environmental changes in aquatic and terrestrial ecosystems. The principal aims were to shed light onto how former human societies and culture shaped and altered their natural environment on the one hand. Furthermore, to reconstruct the once existing environmental conditions within the framework of the natural evolution of the vegetation, soil, fauna and the catchment basin for the times preceding written historical records via the application of sedimentological, geochemical, isotope geochemical, palynological, macrobotanical, malacological and microfaunal analytical methods and approaches.